Typology of non-izosemic realizations of propositional argument (on the material of Polish and Russian language). Part 1 - Kiklewicz, Aleksander (Papers in Linguistics, 2019)
The subject of the article are non-izosemic syntactic realizations of propositional arguments as components of sentence content, implicated by the lexical verb meaning in the position of predicate according to its valence predisposition. The linguistic analysis and description is based on the functional syntactic theory, especially on the explicative syntactic theory, the foundations of which were worked out by S. Karolak, as well as the Polish school of semantic syntax. The author has identified and analyzed in the aspect of functional syntax the following types of syntactic transformations: implication, separation (replacement), loose connection, self-empowerment, conversion, blending, restructuralization, simplification (creation of compact groups), transposition and definitization. The material is served by simple and complex sentences excerpted from the texts as well as the language corpora in Polish and Russian languages; sometimes the information is referred to other languages (for example English). Describing the full/discrete and incomplete/indiscreet syntactic representations of propositional arguments, the author takes into account their three aspects: meaning (semantic function), form (belonging to the grammatical class) and syntactic position (at the verb, at the noun, independent and others).